The Effectiveness of Group Counseling Using the Solution Focused Brief Counseling (SFBC) Approach to Improve Flow in Learning for Islamic Boarding School Students - Mutia Hafizah; Neviyarni S (Jurnal Penelitian Pendidikan IPA, 2025)
Flow in learning is an optimal state when students are fully engaged with focus, motivation, and high levels of satisfaction. However, not all students in Islamic boarding schools are able to achieve this due to academic pressure, environmental adaptation, and concentration difficulties. This study aims to analyze the effectiveness of group counseling using the Solution-Focused Brief Counseling (SFBC) approach in improving student flow in learning. The method used was quantitative research with a quasi-experimental design in the form of a pretest–posttest control group design. The sample consisted of 20 students selected by simple random sampling from a population of 114, then divided into an experimental group (10 students) and a control group (10 students). The experimental group participated in group counseling with the SFBC approach, while the control group received no special treatment. The research instrument used a Likert scale. Data analysis was performed using the Wilcoxon Signed Ranks test to measure changes in each group and the Mann–Whitney U test to compare differences between groups, because the data were not normally distributed. The results showed a significant increase in learning flow in the experimental group after participating in SFBC group counseling, while the control group did not experience significant improvement. Furthermore, there was a significant difference in flow levels between the experimental and control groups. Thus, the SFBC group counseling approach is effective in improving learning flow in Islamic boarding school students.